PRINSIP DAN BENTUK-BENTUK ALTERNATIF PENYELESAIAN SENGKETA DI LUAR PENGADILAN - Marwah M. Diah (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2008)
High legal costs and long delays are some factors that cause individuals to look for alternatives dispute resolution (ADR) to the court adjudication. ADR is un umbrella term which refers generally to alternative to court adjudication of dispute such as negotiation, mediation, conciliation and arbitration. ADR has a lot of advantages in solving the private problems, such as less cost, more freedom, quick result and final and binding as well. Indonesia has UU no. 30/199 tentang Arbitrase dan Penyelesaian Sengketa (ADR), but still ADR need socialization to the societyparticularly to business community.